Episodes of Teaching, Assessing and Testing: Analysis of Teaching Listening in Pakistan (Journal of Asian Development Studies, 2023)
Listening ability helps students to enhance their comprehension level of spoken language. As observed by Ahmed (2016), the students will only get a high-quality score if they listen and understand the teacher attentively. This study aimed to identify the listening proficiency gaps in Pakistani language learning, teaching, and testing systems. The study used Richard's (2008) framework (CLAP) to compare listening tests with student performance. The format and validity of the language proficiency test administered mainly in Pakistan (IELTS) were investigated regarding the teaching and learning practices. All the test takers (15) participated in a standard IELTS listening test with one of their teachers. The results identified three significant factors interfering with listening comprehension performance include, the need for listening assessment in the examination system of schools, colleges, and universities. Secondly, teaching listening depends on theoretical knowledge and need for listening practice in classrooms of second language learners. Further, the study attempted to find evidence to support the claim that Pakistani students can perform better in proficiency scores if presented with it in their teaching and testing system. Accordingly, a model is designed to fill the gaps in learning for language learners as future language teachers in Pakistan. The findings of this study would help design listening performance tests and realize learning potential, devise a listening assessment system, and develop valid large-scale and classroom-based proficiency tests.